Neuroethics across the Disorders of Consciousness Care Continuum - Young, Michael J.; Peterson, Andrew (Seminars in Neurology, 2022)
This review provides an ethical analysis of disorders of consciousness (DoC) along the care continuum, from preinjury to injury, acute care to subacute care and early rehabilitation, and finally transitioning to chronic rehabilitation and societal reintegration. We provide an actionable, chronological assessment of ethical issues related to DoC care. This expands upon established ethics literature, which focuses almost exclusively on the clinical encounter for DoC. Our goal is to broaden the aperture of ethical analysis to address how social and environmental conditions predispose some persons to brain injury, and how such conditions might also pose barriers to meaningful societal reintegration after recovery.
Keywords: disorders of consciousness coma; minimally conscious state brain injury; vegetative state/unresponsive wakefulness syndrome; neuroethics